Tumor-Primed CD3+CD56+ natural Killer T-like Cells As an Efficient Novel Cell Therapy for Relapsed/Refractory Multiple Myeloma - Lee, Ji Hyun; Kim, Seok-Ho; Doh, Junsang; Cho, Duck; Kim, Jeong-a; Oh, Sung Yong; Kim, Sung-Hyun; Lee, Juheon (Blood, 2024)
Introduction Despite the recent development of bispecific antibodies and chimeric antigen receptor T-cell therapies, which have shown promise in the treatment of relapsed/refractory multiple myeloma (RRMM), several limitations remain. NKT-like cells, which is CD1d-independent and express a diverse T cell receptor (TCR) repertoire, have antitumor activity through antigen-specific manner, indicating their ability to recognize antigens similar to conventional T cells. However, there is relatively lack of data on the efficacy of NKT-like cells on RRMM cell lines, and research on the expansion of NKT-like cells in vitro is scarce. The aim of this study was to investigate the possibility of NKT-like cell as a novel treatment approach for patients with RRMM. Methods Tumor-primed CD3+CD56+ NKT-like cell(TPNC)s were generated by co-culture of bone marrow plasma cell(BMPC)s from patients with RRMM and cord blood mononuclear cells after irradiation with 50 Gy X-rays. At an early stage of the co-culture, cells were treated with the cytokine combination which consisted of rhIL-2 (20 ng/mL), rhIL-18 (25 ng/mL), and rhIL-21 (5 ng/mL). In vitro cytotoxicity and degranulation assay were performed using human-derived multiple myeloma cell lines (IM-9 and RPMI-8226). To explore the efficacy of TPNC in vivo, 6-weeks aged female NOD-Prkdc em1Baek Il2rg em1Baek mouse model (NSGA) was used and 7 days after the inoculation of RPMI-8226 cells, vehicle, cytokine-induced killer (CIK) cells, and TPNC cells were intravenously administered at a dose of 5 × 106 cells (N=5 per group). Mice were sacrificed 21 days post-tumor injection during while tumor volumes were measured every 3-4 days. Results In vitro cytotoxicity assay showed the highest E:T ratio (1:10) of autologous patient-sample derived TPNCs in the same patients' BMPCs whereas conventionally expanded CIK cells showed cytotoxicity only against MM cell lines but not for the BMPC samples from the patients with RRMM. These results were replicated in degranulation assays which have shown enhanced degranulation and increased granule synthesis after TPNC treatment compared to CIK treatment. To understand the mechanism underlying the superior cytotoxicity of TPNCs compared to that of CIK cells, we conducted direct observations and quantitative analyses of the interactions between TPNCs or CIK cells and cancer cells. Time-lapse images of CIK/TPNC-cancer cell interactions were quantitatively analyzed, where (i) CIK/TPNC formed a stable engagement with the cancer cell, (ii) polarized lytic granules toward the synapse, (iii) killed the cancer cell, and (iv) detached after killing to find another cancer cell. Overall, TPNCs demonstrated considerably faster granule polarization, shorter killing time, and shorter total interaction time with the target cell line, IM-9, than that of CIK cells. Furthermore, contact frequency analysis revealed that TPNCs tended to release their bound target cells at a higher rate and moved on to the next target cell. Therefore, TPNCs effectively polarized and released cytotoxic granules at the immune synapses into target cells, resulting in faster target cell lysis. In vitro assay using in the NSGA mice inoculated with MM cell lines showed significant differences between TPNC group and vehicle or CIK group in terms of tumor volume and weight after 14 days of vehicle and cell injection. All the mice in the vehicle and CIK group died before day 30, while those in the TPNC group remained viable until day 50. Importantly, no significant toxicity was induced by TPNCs in the treated mice post-administration. CONCLUSION Tumor-primed NKT-like cell (TPNC) has proven its efficacy in vitro and in vivo RRMM models in this study. Notably, it does not require searching for specific tumor-associated antigens while maintaining manufacturing efficiency, and does not require gene editing with viral vectors. Further research on the safety and efficacy of TPNC in human subjects with RRMM is needed and to improve the efficiency and expansion of NKT-like cells by tumor priming is under investigation. Acknowledgements This work was supported by grants from the National Research Foundation (NRF-2022R1F1A1074558, NRF-2023M3A9J4057877) in the Republic of Korea, a grant of the Korea Health Technology R & D Project through the Korea Health Industry Development Institute (KHIDI), funded by the Ministry of Health & Welfare, Republic of Korea (Grant Number:HI22C1363). Lee:Takeda, Amgen, Janssen, Celgene-BMS, Sanofi, Otuka, Pfizer, Celltrion, Boryung, Recordati rare diseases: Honoraria, Speakers Bureau; Takeda, Janssen, Amgen, Celgene-BMS: Consultancy; Amgen, Janssen, JW Pharmaceutical, Otsuka: Research Funding.